(untitled) (Swiss Medical Weekly, 2018)
INTRODUCTION In general practice, the diagnosis of dementia is often delayed. Therefore, the Swiss National Dementia Strategy 2014 concluded that action was needed to improve patient care. Little is known about GPs’ confidence in and approach to the diagnosis, disclosure and post-diagnostic management of individuals with dementia in Switzerland. The aim of this survey is to assess these elements of dementia care and GPs’ views on the adequacy of health care services regarding dementia. MATERIALS AND METHODS Cross-sectional postal survey in Switzerland in 2017 supported by all academic institutes of general practice in Swiss universities. Members of the Swiss Association of General Practitioners (n = 4460) were asked to participate in the survey. In addition to the GPs’ demographic characteristics, the survey addressed the following issues: GPs’ views on the adequacy of health care services, clinical approach and confidence in the management of dementia. RESULTS The survey response rate was 21%. The majority of GPs (64%) felt confident diagnosing dementia, but not in patients with a migration background (15%). For neuropsychological testing, three-quarters of GPs collaborated with memory clinics and were satisfied with the access to diagnostic services. At the time of first diagnosis, 62% of GPs diagnosed the majority of their patients with a mild stage of dementia, and 31% with a mild cognitive impairment. The most frequent actions taken by GPs after the diagnosis of mild dementia were giving advice to relatives (71%), testing fitness-to-drive (66%) and minimising cardiovascular risk factors (63%). While 65% of GPs felt confident taking care of patients with dementia, fewer (53%) felt confident in pharmacological treatment, coping with suicidal ideation (44%) or caring for patients with a migration background (16%). Half of GPs preferred to delegate the assessment of fitness-to-drive to an official authority. One in four GPs was not satisfied with the local provision of care and support facilities for patients with dementia. CONCLUSIONS Overall, GPs reported confidence in establishing a diagnosis of dementia and sufficient access to diagnostic services. Post-diagnostic management primarily focused on counselling and harm reduction rather than pharmacological treatment. Future educational support for GPs should be developed, concentrating on coping with their patients’ suicidal ideation and caring for patients with a migration background.